Signal transduction inhibitors and their use in the cancer treatment, with particular interest to the therapy of acute myeloid leukemia - Deptała, Andrzej; Nurzyńska, Daria (Contemporary Oncology/Współczesna Onkologia, 2001)
Considered as a standard, therapy of acute myeloid leukemia with cytarabine and antracyclins allows to achieve complete remission in the majority of patients. However some of them, who are not eligible for stem cell transplantation, are likely to relapse. The second line treatment is much less effective and does not allow for durable remissions. Hence, the new therapeutics, with novel mechanism of action, are required. In the article we reviewed the process of signal transduction, underlining the role of RAS proteins and protein kinases C. Moreover, the biological and chemical properties of agents that modify the function of mentioned proteins are described, followed by the results of finished to date or currently undergoing clinical trials of the effectiveness of farnesyltransferase inhibitors and protein kinase C downregulators in patients with refractory or relapsed acute myeloid leukemia.